La Sociedad Prehispánica en las Lenguas Náhuatl - Wright Carr, David Charles (Acta Universitaria, 2008)
One tool for constructing a deeper understanding of pre-Hispanic Mesoamerican cultures is to analyze the words used to express various aspects of those cultures. In this article the author uses early colonial period vocabularies to identify the words used by the pre-Hispanic Nahuas and Otomis to express concepts related to their social structures. These terms are analyzed and compared, in order to understand how these groups spoke about their society, and to determine the degree of similarity between their respective semantic fields. The results of this analysis indicate that both groups conceptualized their social structures in essentially the same way, from the basic family unit to the most complex structures, such as the confederations of kingdoms.